4-Nitrophenyl activated esters are superior synthons for indirect radiofluorination of biomolecules. Issue 8 (7th July 2020) - Haskali, Mohammad B.; Farnsworth, Ashleigh L.; Roselt, Peter D.; Hutton, Craig A.
Abstract : A comparative study of PNP- and TFP-activated esters of radiolabelled prosthetic groups demonstrates the superiority of PNP esters in terms of stability and yields for use in one-step radiolabelling of small molecules and peptides. Abstract : Indirect radiolabelling has for a long time been the mainstay strategy for radiofluorination of biomolecules. Acylation of biomolecules through the use of an 18 F-labelled activated ester is a standard method for indirect radiolabelling. However, the preparation of 18 F-labelled activated esters is typically a complex and multistep procedure. Herein, we describe the use of 4-nitrophenyl (PNP) activated esters to rapidly prepare 18 F-labelled acylation synthons in one step. Furthermore, we present a comparative study of PNP activated esters and the commonly utilised 2, 3, 5, 6-tetrafluorphenyl (TFP) activated esters under direct radiofluorination conditions and demonstrate their relative acylation behaviour. We demonstrate the superiority of PNP esters under direct radiofluorination conditions with favourable acylation kinetics.